1972
DOI: 10.1073/pnas.69.3.752
|View full text |Cite
|
Sign up to set email alerts
|

Elongation Factors EF Tu and EF G Interact at Related Sites on Ribosomes

Abstract: The binding of elongation factor EF G to ribosomes inhibits the subsequent reaction of the ribosomes with the ternary complex aminoacyl-tRNA EF Tu GTP. Both the hydrolysis of GTP and the binding of aminoacyl-tRNA to ribosomes are nearly abolished by the previous binding of factor EF G to ribosomes in the presence of either fusidic acid plus either GTP or a nonhydrolyzable analog of GTP. The results suggest that each elongation factor binds to the same region on the ribosome. The GTPase activities of both facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

1973
1973
2010
2010

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…(i) Thiostrepton, an antibiotic that binds to 50S subunits, prevents both the EF-Gand EF-Tu-associated hydrolyses (30). (ii) Protein L7 and/or L12 are required for both reactions (15,16 hydrolytic reactions cannot occur simultaneously on a single ribosome (2,(11)(12)(13). Additionally, it has recently been suggested that GTP hydrolysis during initiation might also involve this ribosomal site (31).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(i) Thiostrepton, an antibiotic that binds to 50S subunits, prevents both the EF-Gand EF-Tu-associated hydrolyses (30). (ii) Protein L7 and/or L12 are required for both reactions (15,16 hydrolytic reactions cannot occur simultaneously on a single ribosome (2,(11)(12)(13). Additionally, it has recently been suggested that GTP hydrolysis during initiation might also involve this ribosomal site (31).…”
Section: Methodsmentioning
confidence: 99%
“…An experimental approach to this problem is provided by the "single step" hydrolysis of GTP by EF-G and the 50S ribosomal subunit in the presence of fusidic acid (9,10). This system is one of the simplest manifestations of GTP participation in protein synthesis, and recent results suggest that it may involve a ribosomal site in common with the other GTP-requiring elongation step of protein synthesis, aminoacyl-tRNA binding (2,(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Translocation of the mRNA:tRNA complex is promoted by the GTPase EF-G in order to vacate the A site so that the next incoming aminoacyl tRNA can be accommodated. Although there is considerable evidence indicating that the elongation factors (and other GTPases involved in the translation cycle) bind to overlapping sites on the ribosome (Cabrer et al 1972;Miller 1972;Richter et al 1972;Moazed et al 1988;Cameron et al 2002;Frank 2003), there must be structural distinctions between the different functional states of the ribosome that allow for their specificity of action (Richman and Bodley 1972;Wool et al 1992;Zavialov and Ehrenberg 2003). Traditionally, pre-translocationstate ribosomes have been characterized by the lack of reactivity of bound peptidyl tRNA substrate with incoming aminoacyl tRNA substrates.…”
Section: Introductionmentioning
confidence: 99%
“…In recent work, these reactions have been used to define the site of action of EF-G on the ribosomal surface (the G site). It appears that the G and A sites overlap on the ribosomal surface, for EF-G and EF-Tu cannot interact simultaneously with the ribosome (11)(12)(13)(14)(15)(16). If so, they must probably alternate in their binding to lpolysomal ribosomes during peptide chain elongation.…”
mentioning
confidence: 99%